Recognizing Emotional Facial Expressions and Lie Detection - Baić, Valentina; Deljkić, Irma; Petrović, Jelena (Kriminalističke teme, 2017)
Reason(s) for writing and research problem(s): Having in mind that the emotion approach plays an important part in understanding verbal and nonverbal cues to deception, and that accurate detection of emotional reactions that may indicate deception is of particular importance for the police investigators, this paper presents the findings of a research on the accuracy of recognition of the emotional facial expressions. Aims of the paper (scientific and/or social): Starting with the assumption that the perception, apperception and the determination of the meaning of especially exogenous sitimuli are very important for communication in the social interaction, and thus for the activity of the police, this paper presents a research whose aim was to ensure answers to the following questions: Are there any differences in the accuracy and time of recognizing emotional facial expressions among respondents; How successful are the respondents in recognizing emotional facial expressions in general, with regard to gender, and with regard to the existence of positive and negative emotions, and in identifying specific emotions? Methodology/Design: The study included 97 respondents (46 men and 51 women), which were students of Police Academy in Belgrade and the Faculty of Medicine in Novi Sad, with the average age of 22 years. Emotional facial expressions that were used in the study were taken from the Karolinska Directed Emotional Faces base (KDEF). A total of 36 photos of emotional expressions was used, of which 18 were photographs of women and 18 of men. After watching successive display of photos on a computer screen, respondents were asked to provide fast and accurate identification of emotions. Research/paper limitations: Research has been conducted in the experimental conditions, so it is assumed that the results would be more objective if research was to be conducted under the real life circumstances. Furthermore, our study included a 36 facial expressions, and this number could be larger in future research. Finally, we also question the motivation of respondents to invest more personal effort to fulfill requirements of the research. Results/Findings: The research results show that the average value of the total accuracy of recognition of emotional expression was 84% (SD = 5.93), and that there are gender differences in the recognition of emotional expressions in favor of women (85%) compared to men (82%). That is, women required less time to perform this task (SD = 51.9) than men (SD = 59.2). Survey results also show that higher scores were achieved significantly in the accuracy of recognition of negative facial expressions compared with the positive expressions (p<.001). In terms of success in the recognition of individual emotion, the research results show that the full performance (100%) was achieved in recognizing emotional expressions of happiness and anger, then in recognizing disgust (84%) and fear (59%), while the lowest success was achieved in recognizing surprises (43%). General conclusion: In the behavior of people who tell the truth or lie, certain changes of emotional or cognitive nature occur. For people who lie, these changes occur because the person first thinks about lying and then tries to lie, which is why certain emotions arise. A person who speaks the truth can display emotions that reflect contextual factors such as concern for the consequences of telling the truth, fear of disbelief, and other. Therefore, a correct approach implies that detection of emotional reactions should be helpful to police investigators in detecting deception and assessing verbal, vocal and nonverbal behavior of a person, and that emotions per se can not be taken as exclusive indicators of lying. Research/paper validity: The communication in the social interaction, in addition to the verbal (vocal), further takes place at the the non-verbal level (body and facial expression), and therefore any research of this matter is important for understanding lie detection.